Love in the Archives: Towards a Theory and Praxis of Archival Care - Douglas, Jennifer (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
The word love is not used very often in archival scholarship or in archival practice. Love is also easy to dismiss as a subject of serious inquiry. This article takes seriously the role of love in archives, engaging with ideas from critical and feminist love studies, where love is understood as a creative and productive force that can be used to bring about transformative change. Drawing on research about grieving and recordkeeping, with both bereaved records creators and practising archivists, and grounded in the expanding critical literature on trauma-informed archival praxis and affect and emotions in archival work, this article considers how the discourse of love is taking shape in archival studies and why any discussion about love in archives has to be grounded in a politics of structural care. Thinking with Tamarin Norwood’s notion of institutional love, the article argues for a kind of love that is research- and experience-led and embedded in institutions, policies, procedures, and training.